Muscle dysfunction in tension-type headache in adolescents and methods of its correction - Stepanchenko K.A. (Medičnì Perspektivi, 2017)
The aim of our study was to investigate the value of myofascial disorders in adolescents with tension-type headaches and evaluation of effectiveness of their treatment using non-drug therapies. A total of 320 adolescents with tension-type headache have been under study. Research of intensity of headache and pain muscle dysfunction was performed. The treatment period was 1 month. We compared treatment by individual adaptive biofeedback based on heart rate variability and pharmacotherapy. Also patients performed the complex of techniques of isometric muscle autocorrection. It was established that with the increase of incidence of headache episodes, the intensity of the local muscle tenderness and the number of muscles, involved in the formation of a painful syndrome increases. Usage of individual adaptive biofeedback was more effective in reducing the severity of muscle dysfunction, than usage of pharmacotherapy, especially in patients with chronic tension-type headache.